Pengaruh Soft Total Quality Management terhadap Kinerja UKM di DKI Jakarta: Pendekatan Balanced Scorecard - Zihni, Aufa Yarzqi; Arif, Helman (UI Scholars Hub, 2023)
This study aims to analyse the effect of Soft Total Quality Management (Soft TQM) on SME performance in Jakarta, both from financial and non-financial perspectives. We used a balanced scorecard (BSC) approach and collected 135 datasets through online surveys to the business owners/manager. Data analysis was carried out by Structural Equation Modelling (SEM) method. The results of the data analysis showed that soft TQM has a negative and not significant effect on SMEs financial perspective, however there is a positive and significant effect on SMEs non-financial perspective. This study also discovered that innovation and leaning perspective mediates the impact of soft TQM on financial perspective in a positive and significant way.